Photodegradation of Nitrogen Oxide under Solar Light Using a Facile Synthesis Catalyst - Ernso Fenelon; Sheng-Jie You; Ya-Fen Wang (Aerosol and Air Quality Research)
Abstract NOx is becoming a hot issue due to its contribution to ozone, PM2.5 formation, and its negative impacts on the ecosystem. In this study, the synthesis of an MgO/Bi2S3-BiOCl composite was carried out via the co-precipitation method for the photodegradation of nitrogen oxide (NO) under solar light. The BiOCl heterojunction is a result of interactions between the Bi2S3 solution and the MgCl2.6H2O precursor. This BiOCl heterojunction provides more available active species that enhance the degradation of NO. The successful synthesis of this composite using a co-precipitation method was confirmed by different characterization analyses (XRD, FTIR, SEM, TEM, DRS, and ESR). The photocatalytic degradation of NO under solar light using 7% MgO/Bi2S3-BiOCl reached an efficiency of 74.6%, which was better than that obtained using pure Bi2S3 (42.8%) and MgO (11.2%). The reusability test showed that the 7% MgO/Bi2S3-BiOCl material was maintained stability in the photodegradation of NO even after five cycles. The trapping test showed that the holes (h+) and hydroxyl (•OH−) were the main active factors in the photodegradation process. The findings of this study confirmed that MgCl2.6H2O is a suitable precursor leading to improvements in the performance of Bi2S3 for the purpose of promoting a new composite that can be used in the photodegradation of NO and could be a candidate for practical applications.